2022
DOI: 10.32615/ps.2022.027
|View full text |Cite
|
Sign up to set email alerts
|

Mitigative effect of 6-benzyladenine on photosynthetic capacity and leaf ultrastructure of maize seedlings under waterlogging stress

Abstract: 6-Benzyladenine (6-BA) is an artificial synthetic cytokinin, which plays an important role in regulating plant responses to abiotic stress. This study aimed to investigate the mitigative effect of exogenous 6-BA on photosynthetic capacities and leaf ultrastructure under waterlogging stress using two waxy corn inbred lines. The results showed that waterlogging stress disrupted the photosynthesis of waxy corn seedlings. However, exogenous 6-BA alleviated the inhibition caused by waterlogging stress. Under the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Our findings indicate that in blueberry there is an increase in chlorophyll a by the application of 6-BAP and a significant increase in chlorophyll a and b and total chlorophyll by the interaction of GLU*6-BAP at higher concentrations ( Table 4 ); these results agree with those reported by El-Metwally et al [ 45 ], as the application of 20 mg L −1 GLU increased the content of chlorophyll a and b and total chlorophyll in peanuts. In contrast, Franzoni et al [ 64 ] and Wang et al [ 33 ] reported that applying GLU and 6-BAP had no positive effect on the chlorophyll content in and yield of lettuce and maize.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our findings indicate that in blueberry there is an increase in chlorophyll a by the application of 6-BAP and a significant increase in chlorophyll a and b and total chlorophyll by the interaction of GLU*6-BAP at higher concentrations ( Table 4 ); these results agree with those reported by El-Metwally et al [ 45 ], as the application of 20 mg L −1 GLU increased the content of chlorophyll a and b and total chlorophyll in peanuts. In contrast, Franzoni et al [ 64 ] and Wang et al [ 33 ] reported that applying GLU and 6-BAP had no positive effect on the chlorophyll content in and yield of lettuce and maize.…”
Section: Discussionmentioning
confidence: 97%
“…Cytokinins such as 6-BAP are plant hormones involved in growth and development, the regulation of cell division processes, the delay in senescence, and the regulation of apical dormancy [ 24 , 25 ]. It was reported that the application of 6-BAP in selected crops favors the production of buds [ 26 , 27 ] and the generation of roots and flowers [ 28 , 29 ], in addition to the removal of reactive oxygen species [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%